2018
DOI: 10.15761/iod.1000201
|View full text |Cite
|
Sign up to set email alerts
|

Long term (3 years) weight loss after low intensity endurance training targeted at the level of maximal muscular lipid oxidation

Abstract: Among various strategies of exercise intensification proposed for the management of obesity and type 2 diabetes, endurance training remains a well recognized procedure. When targeted with exercise calorimetry at levels where lipid oxidation is maximal (LIPOXmax), it has been shown to improve mitochondrial respiration, blood glucose control and blood lipids, low grade inflammation and body composition, even at low weekly volume. We investigated in this study its long term effects over 3 years (3x45 min/week) co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Considering age-related changes in body composition, namely progressive reductions in lean body mass and increases in adipose tissue [32][33][34], such an intensity of NW training in older people seems to be particularly beneficial health-wise [24]. What is interesting, the study conducted by Drapier et al [35] showed that the effects of LIPOXmax training continue to improve body composition within 3 years. The results of our study suggest that the applied procedure is likely to have this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Considering age-related changes in body composition, namely progressive reductions in lean body mass and increases in adipose tissue [32][33][34], such an intensity of NW training in older people seems to be particularly beneficial health-wise [24]. What is interesting, the study conducted by Drapier et al [35] showed that the effects of LIPOXmax training continue to improve body composition within 3 years. The results of our study suggest that the applied procedure is likely to have this effect.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, patients have worse compliance to intensive protocols (Garber et al, ). For these reasons, especially in obese patients, a low‐intensity endurance training targeted at maximal muscular lipid oxidation could be prescribed (Drapier et al, ).…”
Section: How To Prescribe Physical Exercise To Patients With Erectilementioning
confidence: 99%
“…Previous studies have also shown that LIPOXmax training is effi cient by its own for losing weight [28,29] and maintaining this weight loss over several years [30]. This fi nding has been explained by the fact that this type of exercise makes more than an energy defi cit [14], ie, it induces profound changes in eating behavior and in spontaneous physical activity [31].…”
Section: Discussionmentioning
confidence: 99%